Mobile Applications to Improve Emotional Intelligence in Autism – A Review - Papoutsi, Chara; Drigas, Athanasios S.; Skianis, Charalabos (International Journal of Interactive Mobile Technologies (iJIM), 2018)
The ability to understand and regulate emotions in ourselves and others is essential for the healthy development of all human beings. It helps people comprehend themselves and other people, it guides response and decision making and enhances the capacity to develop social relationships. People with Autistic Spectrum Disorders have deficiencies in Emotional Intelligence skills and that leads to difficulties in understanding themselves and the people in their social environments in relation to emotions, feelings and thoughts. The usability of mobile applications developed for children and adolescents with ASD is important because it gives the opportunity to practice in an accessible and creative way to enhance their emotional intelligence. The current article aims to carry out a systematic review of mobile applications on improving emotional intelligence in children and adolescents with Autistic Spectrum Disorders.